Incomplete fissures are associated with increased alveolar ventilation via spiracles in severe emphysema. (6th July 2017) - Khauli, Samih; Abston, Eric; Sajjad, Hassan; Bolukbas, Servet; Lopez, Julio Mott Ancona; Saad Jr, Roberto; Bhatt, Surya P; Eberlein, Michael
Abstract: OBJECTIVES: In emphysema, air can flow preferentially via collateral pathways, which can connect an entire lung when incomplete fissures are present. Spiracles are openings through the chest wall into the lung parenchyma. We previously observed increased alveolar ventilation (VA) in subjects with severe emphysema, when spiracles occurred during lung transplant operations. In this study, we set out to identify a computed tomography (CT) imaging phenotype associated with improved VA via spiracles in severe emphysema. METHODS: We retrospectively reviewed 4 patients with severe emphysema who exhaled ≥75% of the inhaled tidal volume via transpleural spiracles during a lung transplant operation. We used quantitative image analysis via VIDA VISION CT software to describe emphysema severity and distribution and fissure integrity from pretransplant CT scans of the chest. We analysed partial pressure of carbon dioxide and calculated estimates of VA at baseline and during spiracle ventilation. RESULTS: All 4 subjects demonstrated severe hyperinflation (total lung capacity 148 ± 24%predicted, residual volume 296 ± 79% predicted). On CT imaging, severe emphysema was present, with an average 38.7 ± 9% (range 28–50%) of lung parenchyma showing low-attenuation areas of − 950 Hounsfield units or less. Lung fissure integrity analysis demonstrated evidence of incomplete fissures (average detectable fissure integrity 67 ± 19%, range 40 ± 11–90 ± 10%). During spiracle ventilation on unchanged ventilator settings, there was a significant reduction in partial pressure of carbon dioxide (61 ± 4–35 ± 4 mmHg, P  < 0.001) and increase in estimated VA (2.1 ± 0.5–3.8 ± 0.8 l/min, P  < 0.001). CONCLUSIONS: Incomplete lung fissures on quantitative CT analysis seem to be a key image phenotype associated with substantial improvements in VA during transpleural ventilation via spiracles in severe emphysema.